2009
DOI: 10.1016/j.ssc.2009.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Formation of transition metal hydrides at high pressures

Abstract: Silane (SiH 4 ) is found to (partially) decompose at pressures above 50 GPa at room temperature into pure Si and H 2 . The released hydrogen reacts with surrounding metals in the diamond anvil cell to form metal hydrides. A formation of rhenium hydride is observed after the decomposition of silane. From the data of a previous experimental report (Eremets et al., Science 319, 1506), the claimed high-pressure metallic and superconducting phase of silane is identified as platinum hydride, that forms after the de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 35 publications
9
80
1
Order By: Relevance
“…An early form of the AIRSS structure searching method was used to find more stable structures in an overnight run on a standard single processor machine. 31 Structures that we had found of SiH 4 with I4 1 /a and I42d symmetries were subsequently verified by X-ray diffraction experiments, 53,54 although the I4 1 /a phase is insulating, see Fig. 4.…”
Section: Superconducting Hydridessupporting
confidence: 53%
“…An early form of the AIRSS structure searching method was used to find more stable structures in an overnight run on a standard single processor machine. 31 Structures that we had found of SiH 4 with I4 1 /a and I42d symmetries were subsequently verified by X-ray diffraction experiments, 53,54 although the I4 1 /a phase is insulating, see Fig. 4.…”
Section: Superconducting Hydridessupporting
confidence: 53%
“…This polymorph of silane has also a small band-gap as it is opaque in visible light. At 50 GPa silane is observed to become amorphous and partially decompose [6]. This new finding contradicts earlier claims that a metallic phase of silane is formed above 50 GPa [7] -the reported "metallic" phase can most probably be attributed to PtH x (coincidentally obtained from Pt foil used to measure resistance of the sample, and H 2 evolving from silane [6]).…”
Section: Introductioncontrasting
confidence: 57%
“…The use of phonon--guided optimization enables us to further propose that ‡ The X-ray diffraction pattern of F dd2 does not reproduce two new peaks observed for compressed SiH 4 above 25 GPa (Ref. [6]). We notice that these two peaks cannot be unambiguously assigned to a new phase of SiH 4 as Ref.…”
Section: Phonon-guided Optimizationmentioning
confidence: 99%
“…15 This discovery gives a well explanation for the differences between experimental and theoretical studies of high pressure phase of silane. 6,8,10,11,14 The calculated lattice constants, the simulated XRD pattern, and the superconducting transition temperature for platinum hydride are in good agreement with the previously published experimental results.…”
Section: Discussionmentioning
confidence: 81%
“…Degtyareva et al 15 showed that the experimental XRD pattern can be explained by the formation of a platinum hydride due to the reaction of hydrogen (originating from the decomposed silane) with platinum electrodes (used for measuring conductivity). However, the structure and exact composition of this platinum hydride are not determined, and it is still unknown whether platinum hydride(s) can explain peculiar superconductivity observed in Ref.…”
mentioning
confidence: 99%